A Model of Trust within the Mother-Midwife Relationship: A Grounded Theory Approach. (22nd October 2020) - Mirzaee, Firoozeh; Dehghan, Mahlagha
Abstract : Introduction . The mother-midwife relationship is a good experience during childbirth, but there is a lack of evidence about the trustful relationship between mothers and healthcare providers during labor and birth in Iran. The current study aimed to discover how a trustful mother-midwife relationship is formed during a vaginal delivery. Methods . Twenty-nine women who had a vaginal delivery, midwives, and obstetricians participated in this qualitative research with the grounded theory method. Data were collected using semistructured interviews and observations. Open, axial, and selective coding was used for data analysis. Findings . The main category of "seeking trust in midwife" and three subcategories of "effective interaction, " "attempt to access to healthcare provider", and "playing an active role in birth" were extracted from the data. Conclusion . According to the findings, mothers tried to gain action/interaction strategies and increase healthcare providers' trusts during vaginal delivery. It is essential to consider the factors that improve or disrupt this relationship.